How can girls 3rd form transition into a middle school boarding house be made more effective? - Campion, Hannah (2017)
Currently, there is little academic research into the causes of anxiety and transition management in independent boarding schools. This is also a time where managing pupil wellbeing is a top priority following findings that teenagers are experiencing increasing levels of emotional anxieties, particularly during times of change. Therefore, this study focuses on 3rd form girls transition to a Middle School boarding house; School A. The methods used to collect data were questionnaires, interviews and focus groups. A second school was also interviewed, School B, to gain an alternative perspective. Findings revealed the key causes of anxiety were fitting in and making new friends with a delayed anxiety being homesickness related to separation anxieties. There were many methods used to manage 3rd form transition, two being New Girls lunch induction day and House families. A key factor to ensure a successful transition was child-centric planning and its consistency needing support from house staff, girls and parents. Despite many success, School A did show areas for improvement and three areas were focused on, with recommendations for more effective practice. The three areas were: more structured house families, better parent communication and a clearer policy for mobile phone use.